The Role of Corporate Transparency in Moderating the Influence of Fixed Asset Intensity, Leverage, and Profitability on Tax Avoidance in Mining Companies Listed on the Indonesia Stock Exchange from 2020-2024 - Beby Hilda Agustin; Nur Rahmanti Ratih; Dea Ananda Arfianti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Tax avoidance is an important issue for companies in managing their finances, especially for companies in the mining sub-sector that have flexibility in tax planning. The purpose of this study is to analyze the effect of fixed asset intensity, leverage, and profitability on tax avoidance using the moderating variable of transparency in mining sub-sector companies listed on the Indonesia Stock Exchange from 2020 to 2024. The approach used by the researcher in this study is quantitative panel data regression analysis. The model selected for this study is the Random Effect Model (REM), which has undergone several tests, namely the Chow Test, Hausman Test, and Lagrange Multiplier (LM) Test. In this study, the researcher measures tax avoidance using the Effective Tax Rate (ETR), which reflects the actual tax burden borne by the company. The results show that fixed asset intensity does not affect tax avoidance. Meanwhile, leverage can positively affect tax avoidance, and profitability negatively affects tax avoidance. Tax avoidance can only be moderated by corporate transparency in the relationship between leverage and tax avoidance in a weakening direction, but it cannot moderate the variables of fixed asset intensity and profitability on tax avoidance. This study emphasizes the importance of internal company characteristics and the role of transparency as a governance mechanism in suppressing tax avoidance practices. It is recommended that future researchers add different variables and expand the sample size to obtain more comprehensive results with a higher level of generalization.